Intra-articular Opening Osteotomy Combined with Lateral Ligament Reconstruction for Varus Ankle Arthritis - Syed Wasif Ali Shah, Imran Salim Malik, Fraz Noor, Muhammad Zaib Tunio, Muhammad Kashaf Naseer, Zain-Ul-Abideen (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Ankle arthritis is often reported to either secondary to traumatic incidence or in cases of chronic instability of the ligamentous. Other reasons may include primary osteoarthritis or systemic arthropathies including those of rheumatoid or of the gout. Early treatment plan is highly recommended for better quality of life. Objective: To determine the effectiveness of intra-articular opening osteotomy combined with lateral ligament reconstruction for varus ankle arthritis. Study Design: Cross-sectional analytical study. Place and Duration of Study: Department of Orthopaedic, Shaikh Zayed Hospital, Lahore from 1st April 2023 to 30th September 2023. Methodology: Twenty patients (8 left and 12 right ankles) undergoing intra-articular opening osteotomy combined with lateral ligament reconstruction for varus ankle arthritis was enrolled. The age of the patients was between 30-55 years and both genders. At the anteroposterior ankle views (AP) radiological imaging through X-ray machine was performed pre or post-operation of each patient’s ankle as weight bearing. The scan was reviewed through MRI and evaluated on various scoring methods including the American Orthopedic Foot & Ankle Society Ankle-Hindfoot Score (AOFAS-AH), Ankle Osteoarthritis scale (AOS)the visual analogue scale (VAS), the Short From-36 scale (SF-36).The varus type of ankles was surgically corrected through osteotomy by medial longitudinal incision. Results: The majority of the ankle arthritis was presented in the right ankle than the left with a ratio of 12:8 and the majority of the patients were females (75%). After the scan was reviewed through MRI and evaluated on various scoring methods it was recorded that osteotomy combined with lateral ligament reconstruction for varus ankle arthritis resulted in the betterment of the score from 47.8±15.9 to 75.8±12 as pre and post-operative respectively. Similarly, there was a significant improvement noticed in the VAS score from 5.6±1.7 to 2.4±1.8 as well as improvement in the SF-36 and AOS up to a post-operative value of 67.8±14.7 and 28.1±17.8 respectively. Conclusion: Intra-articular opening osteotomy combined with lateral ligament reconstruction to treat varus ankle arthritis is an effective method for medial distal tibial platform erosion. Keywords: Osteotomy; Ankle arthritis; Ligament; Osteophytes.